EP-343 Compliance of Prescription of Intravenous Maintenance Fluids in Acute Surgical Patients According to NICE Guidelines. (9th August 2022) - Morsy, Hesham; Li, Michael; Davidson, Chris; Gu, Kat; Ali, Maryam; Hollingshead, James; Patel, Dharti
Abstract: Aim: Assess compliance of prescription of for intravenous maintenance fluids in accordance with NICE Guidelines in the acute surgical admissions population. Method: Total of 158 patients were included. We collected data prospectively for surgical patients admitted between 25/02/21–18/03/21 (first cycle) & 12/09/2021–4/10/2021 (2nd cycle). Maximum of 5 patients daily randomly selected. Data collected in wards after clerking on Day 1 of admission. Surgical Proforma was used to identify feeding plan for patients. Drug charts used to assess volume and types of intravenous fluids prescribed. Admissions by audit authors were excluded to prevent selection bias. Intervention: Posters in Emergency Assessment Unit and Wards, Teaching to junior doctors, Regular reminder messages to on-call teams. Results: Prescription of Intravenous Maintenance Fluids in Acute Surgical Patients in compliance with NICE guidelines for IV Fluid maintenance rose from 6% to 22% between cycle 1 and 2, respectively. In non-compliant prescriptions, the issue was due to excess volume (73%), sodium and chloride (88%) as well as inadequate potassium (75%) and glucose (40%). Conclusions: Most acute surgical admissions require maintenance fluids. Some patients did not have their weight recorded which is necessary for correct calculation of fluid requirements. Some patients were prescribed maintenance fluids although they were not indicated. Most patients received an excessive fluid volume, sodium & chloride. Most patients received inadequate potassium & glucose. Ward based nursing staff are reluctant to give maintenance fluids containing potassium. More teaching and awareness on correct prescription of maintenance fluids is needed.